Reasonable Limitations, Distinct Society and the Canada Clause: Interpretive Clauses and the Competition for Constitutional Advantage - Riddell, Troy Q.; Morton, F. L. (Canadian Journal of Political Science, 1998)
This article connects the conflict in Canada over formal constitutional amendments—patriation (1982), the Meech Lake (1987) and the Charlottetown (1992) Accords—with constitutional litigation and interpretation. The authors posit that governments and organized social interests compete with and among themselves for constitutional advantage in both forums of constitutional modification, and that outcomes in each forum have predictable consequences for behaviour in the other. Specifically, they argue that conflicts over the “distinct society” (1987) and “Canada” (1992) clauses are best understood as predictable government attempts to regain constitutional resources lost to Charter-based interest groups during the framing of the “reasonable limitation” clause of the Canadian Charter of Rights and Freedoms (1980–1981) and its subsequent judicial operationalization—the “Oakes test” (1986).The conflicts over theses various “interpretative clauses” were not just about “symbolic Status” or “conflicting constitutional visions,” but about winning Charter cases and accumulating legal resources. The authors develop the corollary argument that “advocacy scholarship” has played a complementary role to litigation in “public interest” groups' use of the Charter to challenge government policies., Cet article associe les conflits au Canada au sujet des amendements constitutionals—le rapatriement (1982), les accords de Meech (1987) et de Charlottetown (1992)—aux litiges et interprétations de la Constitution. Les auteurs postulent que les gouvemements et les organisations défendant des intérêts sociaux rivalisent avec et entre eux pour obtenir un avantage constitutionnel dans les deux forums de modification constitutionnel et que les résultats dans chacun d'eux a produit des conséquences prévisibles sur leur comportement dans l'autre. Plus précisément, ils soutiennent que les conflits au sujet des clauses portant sur la société distincte (1987) et les caractéristiques fondamentales du Canada (1992) peuvent être mieux compris si on les considère comme des tentatives de la part des gouvemements pour regagner des resources constitutionnelles perdues au profit des groupes d'intérêt qui ont articul´ leurs revendications autour de la Charte canadienne des droits et libertés au cours du débat portant sur le clause des «limites raisonnables» (1980–1981) ainsi qu'au cours de son opérationalisation judiciaire ultérieure. Les conflits portant sur ces différentes « clauses interprétatives » ne portaient pas uniquement sur le « statut symbolique » ou les « visions constitutionnelles contradictoires », mais aussi sur la nécessité de gagner les causes impliquant la Charte et l'accumulation de ressources légales. Les auteurs mettent de l'avant l'argument corrolaire suivant lequel le «plaidoyer d'érudition » a joué un rôle complémentaire dans l'usage qu'ont fait les groupes d'intérêt de la Charte pour remettre en question les politiques gouvernementales.